2009
DOI: 10.1007/s11695-009-9922-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Respiratory Physical Therapy Treatment in the PACU and Influence on Postoperative Lung Function in Obese Adults

Abstract: Short-term respiratory physiotherapy during the PACU stay promotes more rapid recovery of postoperative lung function in the obese during the first 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 53 publications
0
19
0
2
Order By: Relevance
“…71 Zoremba et al 71 found that obese subjects who undertook postoperative incentive spirometry had better pulse oximetry values than controls had upon first mobilization, and that these subjects recovered lung function significantly faster during their time in the postanesthesia care unit.…”
Section: Respiratory Care In the Postanesthesia Care Unit And Postextmentioning
confidence: 99%
“…71 Zoremba et al 71 found that obese subjects who undertook postoperative incentive spirometry had better pulse oximetry values than controls had upon first mobilization, and that these subjects recovered lung function significantly faster during their time in the postanesthesia care unit.…”
Section: Respiratory Care In the Postanesthesia Care Unit And Postextmentioning
confidence: 99%
“…124 The intervention was carried out in the PACU following tracheal extubation and consisted of repeated sets of incentive spirometry exercises every 15 min for the first two hours after surgery. The intervention group displayed better oxygen saturation in the PACU and at six and 24 hr postoperatively.…”
Section: Optimization Of Lung Function and Oxygenationmentioning
confidence: 99%
“…Zoremba et al randomized 60 obese surgical patients to incentive spirometry starting in recovery, versus no incentive spirometry. 109 The incentive spirometry group had significantly improved oxygenation, functional vital capacity, and peek inspiratory flow compared with the control group. This translates into real clinical outcome improvement.…”
Section: Postoperative Carementioning
confidence: 87%